Optimising network modelling methods for fMRI - Pervaiz, U (2021)
The activity of functional brain networks is responsible for the emergence of time-varying cognition and behaviour. Accordingly, functional connectivity (FC) in fMRI has been shown to be predictive of behavioural traits and psychiatric and neurological conditions.